THE ROLE OF UNIVERSITY GREEN ENTREPRENEURIAL SUPPORT IN INCREASING GREEN ENTREPRENEURIAL INTENTIONS THROUGH GREEN ENTREPRENEURIAL KNOWLEDGE - Budi Karyanto; Hesti Umiyati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to examine and analyze the influence of university green entrepreneurship on green entrepreneurial intentions through green entrepreneurial knowledge. The sample consisted of management students at universities in Tangerang City, using a purposive sampling method, resulting in 67 respondents. The data analysis technique used structural equation modeling-partial least squares (SEM-PLS) version 4. The results of this study found that university green entrepreneurship has a positive and significant effect on green entrepreneurial knowledge, green entrepreneurial knowledge has a positive and significant effect on green entrepreneurial intentions, university green entrepreneurship has a positive and significant effect on green entrepreneurial intentions, and green entrepreneurial knowledge can mediate the effect of university green entrepreneurship on green entrepreneurial intentions. These findings provide novelty because they demonstrate that the green entrepreneurial environment at universities not only directly influences green entrepreneurial intentions but also indirectly through increased green entrepreneurial knowledge. Thus, this study broadens the understanding that the role of universities is not only as a facilitator of academic knowledge but also as a catalyst in creating a generation of green entrepreneurs with awareness, competence, and a sustainability orientation.